Effect of diabetes self-management education (DSME) on glycated hemoglobin (HbA1c) level among patients with T2DM: Systematic review and meta-analysis of randomized controlled trials. Issue 1 (January 2021) - Bekele, Bayu Begashaw; Negash, Samuel; Bogale, Biruk; Tesfaye, Melkamsew; Getachew, Dawit; Weldekidan, Fekede; Balcha, Behailu
Abstract: Background and aims: Type 2 Diabetes mellitus (T2DM) has been a global public health issue causing in physical, financial and psychosocial crises. The aim of this systematic review and meta-analysis (SRMA) was to evaluate the Diabetes Self-Management Education or Support (DSME/S) on glycosylated hemoglobin (HbA1c) among T2DM patients. Methods: This SRMA was made according to preferred reporting Items for systematic review and Meta-analysis (PRISMA) guidelines. The relevant articles were searched from four databases: Cochrane Library, MEDLINE (EBSCOhost), MEDLINE/PubMed and SCOPUS. Quality assessment was carried out. Pooled standard mean difference in HbA1c were calculated to obtain the effect size with random effect assumption. Subgroup analysis was conducted for assessing heterogeneity among the studies. Results: A total of 1312 studies were identified from databases. Among these 25 studies met inclusion criteria. From these 20 were included in the meta-analysis. In meta-analysis a pooled standard mean difference in HbA1c was −0.604 (95% confidence interval = −0.854 -0.353, I 2  = 90.3, p < 0.001). In subgroup analysis a significant reduction was seen among studies with less than four months, upper middle followed by lower middle income countries (LMICs), Western Pacific (WP) followed by Middle Eastern and Northern African (MENA) regions with moderate to substantial heterogeneity. Conclusion: However, there is paucity of studies in underdeveloped countries. Therefore, further studies validated to these contexts are needed to evaluate the DSME effectiveness. Trial registration: PROSPERO database CRD42020124236 . Highlights: DSEM/S effectiveness has rare verdicts in the deprived settings despite its priceless public health importance. About 85% of studies show that Diabetes Self-Management Education was effective in reducing HbA1c among patients with T2DM. More research is needed on Diabetes Self-Management Education in resource limited settings.